The importance of direct foreign investment on development of Iraqi oil industry for the period (2003-3010) - مسلم, حمدية شاكر (Journal of Economics and Administrative Sciences, 2012)
Oil industry played a major role in delineating the course and type o development in both imported and exported Arabic countries alike where its revenues has perform an essential role in forming programs and plans of development on both national and international level in addition to anticipation of future consuming. Iraq, as an oil producer country with a revenues –based economy depends on oil in building its economy totally including its infrastructure having a the greatest conformed reservoir which make the government budget depends largely on oil revenues where its strategic importance lies in funding all aspects of expenders as it is considered the prime source of foreign currency.  The challenges of deterioration in administrative and technical situations Iraq faces due to the years of war and economic sanction imposed which lead to its decline add new challenges represented in corroded oil wells that need huge money of development and increase its productions efficiency which require focusing on encouraging the foreign investments through oil permissions and contracts to be invested internally. But the current contacts in oil investments are the privilege contracts that guarantee exclusive rights for the contracting company in exploring and production which is unsuitable for Iraq, the joint operations contracts which guarantee the participation of the state with the contacted company in exploring and production as well and lastly the services contacts where the state owns all rights of exploring and production though all this type of contracts play a secondary role in serving wells but not for the purposes of investment or strategic development  of oil exploring and extracting that Iraq need currently.